The Effect of Product Quality, Price, and Word of Mouth on Packing Sticker Purchase Decision at CV. Blitz Media Kreasindo Pekanbaru City - Amirudin M. Amin; Rika Angelia; Mukhsin; Pujiono Eddy; Rangga Rahmadian Yuliendi (Journal of Applied Business and Technology, 2022)
This study aims to analyze the effect of product quality, price, and word of mouth on packing sticker purchasing decisions. This research will object of research is all consumers who visit CV. Blitz Media Kreasindo Pekanbaru. In this study, the object of research is all consumers who visit CV. Blitz Media Kreasindo Pekanbaru. The number of samples in this study was determined from the opinion of "Roscoe" so the sample amounted to 122 people. In this study, the technique used in sampling is Non-Probability Sampling. The data collection technique used a questionnaire and the data analysis technique used was multiple linear regression with SPSS. The results of the study explain that product quality and word of mouth have a positive and significant effect, while the price has a negative and significant effect on purchasing decisions for packaging stickers on the CV. Blitz Media Kreasindo Pekanbaru City.